Impact of Bicuspid Aortic Valve on Complications and Death in Infective Endocarditis of Native Aortic Valves - (:unkn) unknown (TEXAS HEART INST, 2009)
We retrospectively investigated the impact of bicuspid aortic valve on the prognosis of patients who had definite infective endocarditis of the native aortic valve. Of 57 patients, a bicuspid aortic valve was present in 22 (43%), the other 29 had tricuspid aortic valves. On average, the patients who had bicuspid valves were younger than those who had tricuspid valves. Patients with a tricuspid valve had larger left atrial diameters and were more likely to have severe mitral regurgitation. Periannular complications, which we detected in 19 patients (37%), were much more common in the patients who had a bicuspid valve (64% vs 17%, P=0.001). The presence of a bicuspid valve was the only significant independent predictor of periannular complications. The in-hospital mortality rate in the bicuspid group was lower than that in the tricuspid group; however, this figure did not reach statistical significance (9% vs 24%, P=0.15). In multivariate analysis, left atrial diameter was the only independent predictor associated with an increased risk of death (hazard ratio, 2.19; 95% confidence interval, 1.1-4.5; P=0.031). In our study, patients with infective endocarditis in a bicuspid aortic valve were younger and had a higher incidence of periannular complications. Although a worse prognosis has been reported previously, we found that infective endocarditis in a native bicuspid aortic valve is not likely to increase the risk of death in comparison with infective endocarditis in native tricuspid aortic valves. (Tex Heart Inst J 2009,36(2):111-6)
Keywords: Aortic valve/abnormalities/pathology/ultrasonography; aortic valve insufficiency/classification/diagnosis; echocardiography/methods; endocarditis, bacterial/complications/mortality/pathology/ultra-sonography; heart defects/congenital; heart diseases/complications; heart valve diseases/classification/complications/congenital/pathology; hospital mortality; retrospective studies; risk factors; ECHOCARDIOGRAPHY; TRANSESOPHAGEAL; INSUFFICIENCY; REGURGITATION; DIAGNOSIS; RISK